Relations Between Stress Level With Recurrence Of Hypertension Disease To Patients Aged 40-60 Years Old In Community Health Center Level II Municipality Lospalos, Timor Leste - Alexandra Maria Pires; Maximiano Oqui; Virgilio Soares; Benito Oliveira F. Xavier; Tata Mahyuvi (Journal of Applied Nursing and Health, 2022)
Background: For people who get a kind of disease, the medic diagnosis of Hypertension is when their blood pressure is >140/90 mmHg. Those factors that influence added blood pressure are lifestyles, such as smoking, salt intake, obesity, physical activity and stress, genetic factor, inadequate vasoconstriction modulator, vasodilatation, renin system, angiotensin, and aldosterone. The objective of this research is to analyze the “Relationship between stress level with recurrence of Hypertension disease to a patient aged 40-60 years old in Centro Saúde Comunitária Nível II Lospalos, in  2022 years”. Methods: This research uses the quantitative method and cross-sectional approximation conducted in Centro Saúde Comunitária Nível II Lospalos in 2022. The population to be sampled is Hypertension patients aged 40-60 years old, and the sampling result is defined as 91. For technique data collection, the researcher uses a questionnaire. Analyze data technique uses the chi quadrat statistic test. Results: The result of analyzing Chi-Square defined by this research is a significate value of 0.016<0.05 significate unacceptable Ho, and also results by Shi-Square Linear-by-Linear Association of statistic 0.399 meaning less relationship between stress level with recurrence of Hypertension disease to the patient with aged 40-60 years old. The results of Chi-Square have a relationship between stress level and recurrence of Hypertension disease to patients aged 40-60 years old. Conclusion: Stress level is the main risk of recurrence of hypertension. When stress to the patient's recurrence of Hypertension will occur another complication, hypertension is also a kind of disease that is very dangerous to distribute and cause mortality. Hypertension sometimes, other people call silence killer.